Potential drug interactions associated with treatments for Type 2 diabetes and its comorbidities: a clinical pharmacology review. Issue 1 (January 2012) - Freeman, Jeffrey S; Gross, Benjamin
Type 2 diabetes is a disease of glucose metabolism that commonly involves multiple comorbidities, including lipid dyscrasias and hypertension. Each concurrent disorder contributes some risk of complications and requires therapeutic intervention. The simultaneous management of so many coexisting illnesses can be complex and commonly results in patients being prescribed multiple medications – referred to as polypharmacy – which may further complicate treatment. To ensure the best patient outcomes, the treating physician must be aware of all the therapeutic agents that a patient is taking to assess possible drug interactions that such a plethora of medications may confer. This article addresses the underlying comorbidites, the drugs commonly used to treat them and the interactions that may arise from concomitant administration.